Birds of a feather flock together: a dataset for Clock and Adcyap1 genes from migration genetics studies - Le Clercq, Louis-Stéphane; Bazzi, Gaia; Obiol, Joan Ferrer; Cecere, Jacopo G.; Gianfranceschi, Luca; Grobler, J. Paul; Kotzé, Antoinette; Riutort León, Marta; González-Solís, Jacob; Rubolini, Diego; Liedvogel, Miriam; Dalton, Desiré Lee (Nature Research, 2023)
Birds in seasonal habitats rely on intricate strategies for optimal timing of migrations. This is governed by environmental cues, including photoperiod. Genetic factors affecting intrinsic timekeeping mechanisms, such as circadian clock genes, have been explored, yielding inconsistent findings with potential lineage-dependency. To clarify this evidence, a systematic review and phylogenetic reanalysis was done. This descriptor outlines the methodology for sourcing, screening, and processing relevant literature and data. PRISMA guidelines were followed, ultimately including 66 studies, with 34 focusing on candidate genes at the genotype-phenotype interface. Studies were clustered using bibliographic coupling and citation network analysis, alongside scientometric analyses by publication year and location. Data was retrieved for allele data from databases, article supplements, and direct author communications. The dataset, version 1.0.2, encompasses data from 52 species, with 46 species for the Clock gene and 43 for the Adcyap1 gene. This dataset, featuring data from over 8000 birds, constitutes the most extensive cross-species collection for these candidate genes, used in studies investigating gene polymorphisms and seasonal bird migration.